Immigrants and Mental Health - Douki, Stamatina; Spyridakis, Emmanouil (HAPSc Policy Briefs Series, 2024)
The migration process resembles a mourning process, as individuals separate from their family, country, and culture. The purpose of this work is to investigate immigrants' mental health in order to emphasize its importance. A review of international literature was conducted using the PubMed and Google Scholar databases in both English and Greek. The findings of the international literature appear to differ regarding the impact of the immigration process on the increased likelihood of mental illnesses among immigrants. However, it became clear that emphasizing the importance of immigrants' mental health can contribute to the development of appropriate policy interventions aimed at gradually achieving their smooth integration into host countries.